The Effectiveness of a training program based on the six Thinking hats in the academic achievement in the Arabic language in the seventh primary students in Jordan - Almhairat, Raed Hamad; Al-Rabihat, Ghadeer Abdullah Atta (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the effectiveness of a training program based on the six Thinking hats in the academic achievement in the Arabic language in the seventh primary students in Jordan. The study used the semi-experimental method on a sample of 60 students randomly distributed to two control and experimental groups, The achievement test was carried out in both groups. The results of the study showed that there were statistically significant differences at the level of (0.05 = α) between the experimental and control group averages for the experimental group. This means that the six hats were used to raise the level of achievement among the seventh grade students in the Arabic language compared to the normal method.
Keywords: effectiveness; training program; Six Thinking Hats; Academic achievement; Arabic language; seventh grade students; Jordan